2016
DOI: 10.1098/rsif.2015.0986
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite formation on graphene oxide modified with amino acids: arginine versus glutamic acid

Abstract: Hydroxyapatite (HA, Ca 5 (PO 4 ) 3 OH) is the main inorganic component of hard tissues, such as bone and dentine. HA nucleation involves a set of negatively charged phosphorylated proteins known as non-collagenous proteins (NCPs). These proteins attract Ca 2þ and PO 4 32 ions and increase the local supersaturation to a level required for HA precipitation. Polar and charged amino acids (AAs) are highly expressed in NCPs, and seem to be responsible for the mineralizing effect of NCPs; however, the individual eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 71 publications
5
21
0
Order By: Relevance
“…In that case, CaP nucleation probably occurred on the surface of glass particles present on the GS surface of composites in accordance with mechanism of bioactivity proposed by Kokubo and Hench [36]. It was previously shown that the layers of proteins and amino acids on the surfaces of graphene oxide and polymers (PS, PMMA) induced the nucleation of hydroxyapatite in SBF and 1.5SBF [37,38], which can explain the enrichment of pure PCL film surface with Ca and P ( Fig. 1) with an accompanying decrease in Ca and P concentration in DMEM-10% FBS (Fig.…”
Section: In Vitro Bioactivitysupporting
confidence: 54%
“…In that case, CaP nucleation probably occurred on the surface of glass particles present on the GS surface of composites in accordance with mechanism of bioactivity proposed by Kokubo and Hench [36]. It was previously shown that the layers of proteins and amino acids on the surfaces of graphene oxide and polymers (PS, PMMA) induced the nucleation of hydroxyapatite in SBF and 1.5SBF [37,38], which can explain the enrichment of pure PCL film surface with Ca and P ( Fig. 1) with an accompanying decrease in Ca and P concentration in DMEM-10% FBS (Fig.…”
Section: In Vitro Bioactivitysupporting
confidence: 54%
“…The ability of a substrate to self‐mineralize, via selected adsorption of elements from the surrounding environment is a significantly beneficial material property in the development of biomimetic surfaces. The role of surface modification, specifically –NH 2 and –COOH modified layers, in enhancing the ability of a material to produce an apatite‐like layer when submerged in stimulated body fluids has previously been reported . Yet, the role of varying the chain length with a view to optimizing this process has not previously been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The common functional methods of GDs used in bone repair were carboxylation, 103 – 105 silanization, 106 , 107 hydroxylation, 25 dopamine modification 108 , 109 and amination, 24 , 110 as shown in Table 1 . These functional modifications improved the different properties of the composites, such as binding other ions, dispersibility, hydrophilicity, adsorption of serum proteins and attraction to osteoblasts.…”
Section: Utilization Of Advantages Of Gds In Bone Repair Materialsmentioning
confidence: 99%